Пищевая химия: учебник для вузов - Нечаев А. П. Алексей Петрович; Траубенберг С. Е. Светлана Евгеньевна; Кочеткова А. А. Алла Алексеевна; Колпакова В. В. Валентина Васильевна; Витол И. С. Ирина Сергеевна; Кобелева И. Б. Ирина Борисовна (СПб., ГИОРД, 2004)
Авт. указ. на обороте тит. л.